Toward an ethical turn of the technology: why Hans Jonas is not a technophobic - Oliveira, Jelson Roberto de (2022)
The purpose of this article is to counter against the accusation of technophobic, wrongly directed to Hans Jonas, his proposal for an ethical turn of technology, whose bases would be on the ethical capacity to impose restraint on the utopian advance of technical progress, something that leads to the ethics of responsibility to the controversial concept of “heuristic of fear”. To do so, we started from an examination of the Jonasian project of a philosophy of technology, whose third perspective would be valuable, which is the one he developed best. From there, we will analyze what would be the value of technology from the point of view of life (in its four spheres: present and future, human and extra-human) and then strategically analyze the position of Gerard Lebrun for whom Jonas should be placed among technophobic philosophers. Our aim, in this case, is to demonstrate the inconsistency of such an interpretation, precisely because the French thinker with an important presence in Brazil, confuses the proposal of ethical reorientation (in the sense of a power from inside of the technique) with the imposition of an external power, of a paralyzing type.